Perancangan Sepeda Air Low Cost sebagai Sarana Tempat Wisata di Banjir Kanal Semarang - Rifky Ismail; Rizal Mustofa; Yahya Fikri Dwiyanto (Asian Journal of Innovation and Entrepreneurship, 2022)
The Sungai Banjir Kanal Barat is currently one of the attractions for the residents of Semarang City, but currently the Sungai Banjir Kanal Barat still does not have water attractions, one of which is a water bike ride. The design this time tries to make a water bike design that is suitable for water recreation in the Sungai Banjir Kanal Barat area of ​​Semarang City. In the design process, the design is carried out using Solidworks 2021 software and motion analysis is carried out on the transmission system. In addition, the design of this water bike is also equipped with material selection according to the conditions in the West Flood Canal River, Semarang City. Before designing the design, the author reviews several variations of the concept, then the author chooses the best concept to be used as a design design. The selected concept product weighs 67 kg, length 180 cm, width 120 cm, and height 90 cm. Most of the selected concept products use carbon steel material, and use PVC pipe as a float.